Mapping Cancer in Africa: A Comprehensive and Comparable Characterization of 34 Cancer Types Using Estimates From GLOBOCAN 2020 - Sharma, Rajesh; Aashima; Nanda, Mehak; Fronterre, Claudio; Sewagudde, Paul; Ssentongo, Anna E.; Yenney, Kelsey; Arhin, Nina D.; Oh, John; Amponsah-Manu, Forster; Ssentongo, Paddy (Frontiers in Public Health, 2022)
Objective Cancer incidence and mortality rates in Africa are rising, yet their geographic distribution and determinants are incompletely characterized. The present study aims to establish the spatial epidemiology of cancer burden in Africa and delineate the association between cancer burden and the country-level socioeconomic status. Methods The estimates of age, sex, and country-specific incidence and mortality of 34 neoplasms in 54 African countries were procured from GLOBOCAN 2020. Mortality-to-incidence ratio (MIR) was employed as a proxy indicator of 5-year survival rates, and the socioeconomic development of each country was measured using its human development index (HDI). Maps were generated for each cancer group for each country in Africa. Results In Africa, an estimated 1.1 million new cases [95% UI 1.0 – 1.3 million] and 711,429 [611,604 – 827,547] deaths occurred due to neoplasms in 2020. The age-standardized incidence rate (ASIR) was estimated to be 132.1/100,000, varying from 79.5/100,000 (Gambia) to 209.5/100,000 (South Africa) in 2020. The age-standardized mortality rate was 88.8/100,000 in Africa, ranging from 56.0/100,000 in Congo to 139.4/100,000 in Zimbabwe. The MIR for Africa was 0.64, varying from 0.49 in Mauritius to 0.78 in The Gambia. HDI explained 75% of the variation in overall 5-year cancer survival. By 2040, the burden of all neoplasms combined is forecasted to increase to 2.1 million cases and 1.4 million deaths. Conclusion High cancer mortality rates in Africa demand a holistic approach towards cancer control and management, including, but not limited to, boosting cancer awareness, adopting primary and secondary prevention, mitigating risk factors, and improving cancer infrastructure.